A combined computational and functional approach identifies FBLN5 as an amino acid metabolism-related gene and suppressing colorectal cancer progression - Jiezhi Chen; Yang Bai; Shiyi Liu; Changwei Lin (Molecular Genetics and Genomics, 2026)

Pericyte NNMT drives an immune-hostile vascular niche and restricts cancer immunotherapy - Sheng Wang; Geni Ye; Caiyun Zhang; Lin Tan; Zhang Zhang; Xi Xu; Xinhui Chen; Yiming Zhang; Xiaoling Xu; Jinghua Pan; Tong Lan; Junqiu Zhang; et al. (Science Bulletin, 2026)

Coseismic landslide susceptibility modelling via machine learning associated with the September 5, 2022, Luding Mw 6.8 earthquake, southeastern Tibetan Plateau - Lin Deng; Hu Wang; Kaijin Li; Changwei Shen (Bulletin of Engineering Geology and the Environment, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

Dynamic Ni0-Niδ+ cycling promotes the activity and stability of a NixMgyO catalyst for CO2/CH4 reforming - Wuji Lai; Shimin Yan; Jiahao Lu; Yue Ding; Li Li; Wenju Jiang; Zhongde Dai; Lin Yang; Junfeng Zheng; Shenggui Ma; Changwei Hu; Lu Yao (Chemical Engineering Journal, 2026)

Genome-wide analysis of NAC gene family in Brassica campestris ssp. chinensis and characterization of BcNAC134 - Shuilin Yuan; YingXin Lin; Yuan Wang; Changwei Zhang; Dong Xiao; Xilin Hou; Ying Li (Plant Cell Reports, 2025)

CEP78 regulates the proliferation and angiogenesis of endothelial cells by mediating microtubule stabilization via p150glued - Gang Li; Ze Zhao; Changwei Xie; Dong Lin; Wenrui Li; Xing Chen; Kaidi Ren; Yi Zhao (Journal of Molecular Histology, 2025)

Emergence and traceability of Salmonella enterica serotype Mbandaka harboring blaOXA-10 from chickens in China - Ke Wu; Jian Yang; Tiejun Zhang; Jing Zuo; Heng Lin; Juan Wang; Anyun Zhang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2025)

New biological strategies for preventing and controlling food contaminants in the supply chain: Smart use of common plant-derived substances - Changwei Liu; Lu Liu; Haiyan Lin; Senwen Deng; Hongzhe Zeng; Xin Shi; Zhixiang Ling; Fang Zhou; Zhonghua Liu; Shiyin Guo (Food Chemistry, 2025)

The surface features and internal structure of an integrated open system pingo in the source area of the Yangtze River on the Qinghai-Tibet Plateau - Guangyue Liu; Yao Xiao; Guojie Hu; Tonghua Wu; Xiaodong Wu; Lingxiao Wang; Changwei Xie; Defu Zou; Erji Du; Yonghua Zhao; Yingying Lu; Lin Zhao (CATENA, 2025)

Establishment and identification of spleen cell line from tiger puffer fish (Takifugu rubripes) and immune transcriptome response to IHNV - Yangbin He; Jingjing Zhang; Lei Lin; Bo Meng; Caichao Dong; Yuyan Liu; Yu Yang; Honglong Ji; Kaiqiang Liu; Qian Wang; Changwei Shao (Fish & Shellfish Immunology, 2025)

Windfarm construction alters soil multinutrient cycling by destabilizing microfauna community in a mountain ecosystem - Debao Li; Changwei Ma; Chunyu Yue; Na Lin; Yingmo Zhu; Jianping Wu (Journal of Environmental Management, 2025)

Transmission of carbapenem-resistant enterobacterales producing NDM-5 during the broiler breeding process in China - Ke Wu; Yuanyuan Zhang; Wei Xu; Xiaolong Lin; Cui Li; Juan Wang; Ruichao Li; Yizhi Tang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2024)

Three-dimensional freeze-casting solar evaporator for highly efficient water evaporation and high salinity desalination - Bo Li; Mengxiao Lin; Changwei Cheng; Xiangfeng Li (Desalination, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Overexpression of long noncoding RNA MCM3AP-AS1 promotes osteogenic differentiation of dental pulp stem cells via miR-143-3p/IGFBP5 axis - Changwei Yang; Xuehong Xu; Pingting Lin; Bizhu Luo; Shufang Luo; Honglan Huang; Jianyu Zhu; Meie Huang; Shuhai Peng; Qianju Wu; Lu Yin (Human Cell, 2022)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Estimation of ground temperatures in permafrost regions of the Qinghai-Tibetan Plateau from climatic variables - Guojie Hu; Lin Zhao; Ren Li; Xiaodong Wu; Tonghua Wu; Changwei Xie; Xiaofan Zhu; Junming Hao (Theoretical and Applied Climatology, 2020)

Thermal properties of active layer in permafrost regions with different vegetation types on the Qinghai-Tibetan Plateau - Guojie Hu; Lin Zhao; Ren Li; Xiaodong Wu; Tonghua Wu; Changwei Xie; Xiaofan Zhu; Junming Hao (Theoretical and Applied Climatology, 2020)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Modeling of a Space Heating System Coupled with Underground Energy Storage - Guoxiang Zhao; Kewen Li; Changwei Liu; Lin Jia; Bheki Mahlalela Mahlalela (Mathematical Geosciences, 2019)

Propionibacterium acnes induces discogenic low back pain via stimulating nucleus pulposus cells to secrete pro-algesic factor of IL-8/CINC-1 through TLR2–NF-κB p65 pathway - Yucheng Jiao; Ye Yuan; Yazhou Lin; Zezhu Zhou; Yuehuan Zheng; Wenjian Wu; Guoqing Tang; Yong Chen; Jiaqi Xiao; Changwei Li; Zhe Chen; Peng Cao (Journal of Molecular Medicine, 2019)

An improved model for soil surface temperature from air temperature in permafrost regions of Qinghai-Xizang (Tibet) Plateau of China - Guojie Hu; Xiaodong Wu; Lin Zhao; Ren Li; Tonghua Wu; Changwei Xie; Qiangqiang Pang; Guodong Cheng (Meteorology and Atmospheric Physics, 2017)

A20 reduces lipid storage and inflammation in hypertrophic adipocytes via p38 and Akt signaling - Luoyan Ai; Xiaohan Wang; Zhiwei Chen; Qing Lin; Dazhi Su; Qingqing Xu; Changwei Wu; Xiaoke Jiang; Antao Xu; Zhuping Fan (Molecular and Cellular Biochemistry, 2016)

Modeling permafrost properties in the Qinghai-Xizang (Tibet) Plateau - GuoJie Hu; Lin Zhao; XiaoDong Wu; Ren Li; TongHua Wu; ChangWei Xie; QiangQiang Pang; Yao Xiao; WangPing Li; YongPing Qiao; JianZong Shi (Science China Earth Sciences, 2015)

Recent ground surface warming and its effects on permafrost on the central Qinghai‐Tibet Plateau - Tonghua Wu; Lin Zhao; Ren Li; Qinxue Wang; Changwei Xie; Qiangqiang Pang (International Journal of Climatology, 2013)
In this study, the ground surface temperature (GST) records from 16 meteorological stations, which are located in or adjacent to permafrost regions on the central Qinghai‐Tibet Plateau (QTP), are analysed using Mann–Kendal test and Sen's slope estimate methods. We revealed that the GSTs have shown statistically significant warming. On average, mean annual ground surface temperature has increased at a rate of 0.60 °C decade −1 over the period of 1980–2007, which is more pronounced than the increase of mean annual air temperature on the plateau. The winter ground surface warming is especially prominent, which is similar to the seasonal trends in changes of air temperature. As important parameters to assess the changes of ground thermal regime in cold regions, surface freezing and thawing indices were also studied. The nonparametric statistic test and estimate indicate that surface freezing and thawing indices both show significant variations (−111.2 and 125.0 °C d decade −1 , respectively) on the central QTP. The intensive ground surface warming is responsible for the concurrent increase in permafrost temperatures at the long‐term observation sites on the plateau. The close correlations between ground surface and permafrost temperatures indicate that the dramatic ground surface warming could have significant influence on the change of permafrost thermal regime in the study region. Copyright © 2012 Royal Meteorological Society

Evaluating DEM source and resolution uncertainties in the Soil and Water Assessment Tool - Shengpan Lin; Changwei Jing; Neil A. Coles; Vincent Chaplot; Nathan J. Moore; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2013)

Spatiotemporal dynamics of soil erosion risk for Anji County, China - Zhenlan Jiang; Shiliang Su; Changwei Jing; Shengpan Lin; Xufeng Fei; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2012)

Changes in the thermal and hydraulic regime within the active layer in the Qinghai-Tibet Plateau - Changwei Xie; Lin Zhao; Tonghua Wu; Xicheng Dong (Journal of Mountain Science, 2012)